Distribution of human muscle fibre type - Colling, R. (1997)
The classification of human muscle fibre types can be seen as multifactorial . To simplify matters these fibres will first be discussed in terms of contractile ability. In summary, muscles are dynamic functional units. They function in accordance to their structure, and they also respond by altering their structure according to the functional demands. For instance, a trained muscle will hypertrophy in accordance to its training and an immobilized muscle will atrophy. It seems that with the right training of muscle Type IIb can be converted to Type IIa (Andersen & Henricksson, 1977a), and Type I can decrease with a relative increase in Type IIc (Jansson et al, 1978). However, it is impossible to be able to predict performance on the grounds of hypertrophy or percentage of muscle types. Due to the complexity of most functional and sporting activities there are a number of physiological and psychological factors that comprise each performance, therefore muscle fibre type is just one small piece of an extremely complex jigsaw (Howald, 1982).